Fungsi Pemerintah Desa Dalam Pemenuhan Air Bersih Di Desa Bolua Kecamatan Raijua Kabupaten Sabu Raijua - Djami Pau, Rahel; Nuban, Detji K E R; Asnawi, Norani (Law Faculty, Nusa Cendana University, 2025)
Based on Article 67 paragraph (2) letter b of Law Number 3 of 2024 concerning the second amendment to Law Number 6 of 2014 concerning Villages, it is stated that the Village is obliged to